2023
DOI: 10.1002/pro.4778
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptide database is 20 years old: Recent developments and future directions

Guangshun Wang

Abstract: In 2023, the Antimicrobial Peptide Database (currently available at https://aps.unmc.edu) is 20‐years‐old. The timeline for the APD expansion in peptide entries, classification methods, search functions, post‐translational modifications, binding targets, and mechanisms of action of antimicrobial peptides (AMPs) has been summarized in our previous Protein Science paper. This article highlights new database additions and findings. To facilitate antimicrobial development to combat drug‐resistant pathogens, the AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 97 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…The category of microbial AMPs is very broad, covering natural AMPs from four kingdoms of life (bacteria, archaea, protists, and fungi) as annotated in APD (Wang et al, 2016 ; Santos-Júnior et al, 2023 ; Wang, 2023 ; https://aps.unmc.edu ). Most of them share natural druggability properties similar to traditional microbial antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The category of microbial AMPs is very broad, covering natural AMPs from four kingdoms of life (bacteria, archaea, protists, and fungi) as annotated in APD (Wang et al, 2016 ; Santos-Júnior et al, 2023 ; Wang, 2023 ; https://aps.unmc.edu ). Most of them share natural druggability properties similar to traditional microbial antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Databases of thousands of natural and synthetic AMPs are now available, facilitating computationally aided de novo generation and optimization of these compounds. Recent studies have shown the design principles that can be applied to identify stable, active, and nontoxic AMPs for treating infections, as well as to further increase the efficiency of existing compounds (Wang, 2023 ). Most of the AMPs developed to date are natural compounds derived from animals, plants, and microorganisms (Ji et al, 2024 ).…”
Section: Proteins and Peptides As Therapeutic Optionsmentioning
confidence: 99%